An intervention using morphology to derive word meanings for English language learners. Issue 2 (29th January 2019) - Davidson, Sean J.; O'Connor, Rollanda E.
Abstract : Many English language learners (ELL) experience academic and reading difficulties compared to native English speakers (NES). Lack of vocabulary knowledge is a contributing factor for these difficulties. Teaching students to analyze words into their constituent morphemes (meaningful word units) in order to determine the meaning of words may be an avenue to increase vocabulary knowledge. This study investigated potential benefits of morphological instruction for learning vocabulary words and generalizing taught words to untaught words containing these morphemes. Nine fourth‐ and fifth‐grade ELL with reading difficulties participated in a multiple baseline, single‐case design study. Visual analysis of the results revealed a functional relation between the intervention and an increase in participants' vocabulary scores with 90% to 100% nonoverlapping data for eight participants. The effects of training generalized to untaught words. These findings suggest that morphological analysis is a promising approach to increase vocabulary knowledge of ELL.